Diseño de un programa difusivo de prevención y atención de enfermedades para los adultos mayores del Subcentro Patria Nueva - Banegas Ogoño, Daycy Elizabeth (My University, 2019)
One of the elements that every person wants to have is the health that allows the individual to perform their daily and work activities to meet their basic needs. However, a vulnerable group of our society is the elderly who need an essential attention and requirements such as food, stability in social relationships, clothing, leisure time, recreation and respect their human rights. It is important to emphasize that in this stage a high percentage of this group of people is in an economic situation of poverty and sometimes extreme poverty, and in many cases do not lead a life according to the necessary care for this age, and therefore do not lead a life of quality and worthy Becoming a need for older adults to have access to permanent information on issues related to the care of their diseases and their prevention through a healthy diet according to age. It is important that the State as well as the municipal institutions collaborate with the dissemination to improve the health of this vulnerable group. The importance of this research is manifested in the need for older adults to have a program that is aimed at preventing diseases and accessing health care services. The objective of the research is to design a diffusive program of prevention and attention of diseases for the elderly of the Patria Nueva subcenter.. The specific objectives are: to design dissemination plan strategies; choose the means of communication for the broadcast program. As part of the investigation, the descriptive method was applied to access information that was used to prepare the dissemination program. The technique used was the bibliographical one that allowed the compilation of the information contained in magazines and scientific articles, books, internet.
Uno de los elementos que toda persona desea tener es la salud que le permite al individuo poder realizar sus actividades diarias y laborales para suplir sus necesidades básicas. Sin embargo un grupo vulnerable de nuestra sociedad es el adulto mayor quienes necesitan de una atención y requisitos indispensable como alimentos, estabilidad en relaciones sociales, vestimenta, tiempo para el ocio, recreación y que respeten sus derechos humanos. Convirtiéndose en una necesidad que los adultos mayores tengan acceso a información permanente sobre temas relacionados a la atención de sus enfermedades y su prevención a través de una alimentación sana acorde a la edad. Es importante que el Estado así como las instituciones municipales colabore con la difusión para mejorar la salud de este grupo vulnerable. La importancia de esta investigación se manifiesta en la necesidad de un programa que este encaminado a prevenir enfermedades y que acceder a servicios de atención de su salud. El objetivo de la investigación es diseñar un programa difusivo de prevención y atención de enfermedades para los adultos mayores del subcentro Patria Nueva. Como parte de la investigación se aplicará el método descriptivo para acceder a información que sirva para la elaboración del programa de difusión. A partir de aquello la técnica utilizada fue la bibliográfica teniendo como soporte la aportación de la literatura científica de varios autores esto sirvió para recopilar información documental necesaria.
Keywords: ADULTO MAYOR; PREVENCION; ENFERMEDAD; SALUD